Non-Vitamin K Oral Anticoagulants Assessment in High Risk of Bleeding Patients with Non-Valvular Atrial Fibrillation - Silva Cunha, P (2022)
Atrial fibrillation (AF) is commonly associated with advanced age and the presence of multiple, concomitant acute and chronic health conditions, placing this population at high risk for serious therapeutic side effects. Nonvitamin K antagonist oral anticoagulants (NOACs) are increasingly used for stroke prevention in patients with atrial fibrillation. The purpose of this study was to investigate the effectiveness and safety of NOAC in a group at high risk of bleeding complications, in a real-world setting. We conducted a retrospective analysis of a high-risk cohort of 418 patients (pts) followed-up in our anticoagulation unit; data on patient characteristics, anticoagulation treatment, and bleeding and thrombotic complications were evaluated. The population had a median age of 77.8 ± 10.3 years and the mean CHA2DS2-VASc score was 3.85 (SD ± 1.4). Overall, 289 (69.1%) were ≥75 years old. During a mean follow-up time of 51.2 ± 35.7 months, we observed a rate of any bleeding of 7, a clinically relevant non-major bleeding rate of 4.8, a major bleeding rate of 2.2, a stroke rate of 1.6, and a rate of thrombotic events of 0.28 per 100 patient-years. There were 59 hospitalizations due to any cause (14.1%) and 36 (8.6%) deaths (one due to ischemic stroke). A structured follow-up, with judicious prescribing and drug compliance, may contribute to preventing potential complications